A zeolite-based ship-in-a-bottle route to ultrasmall carbon dots for live cell labeling and bioimaging. Issue 12 (9th November 2020) - Dong, Lei; Hu, Dehong; Wang, Yanding; Sheng, Zonghai; Hong, Mei; Yang, Shihe
Abstract : The smallest-pore SAPO-20 zeolite confined pyrolysis of organics afforded ultrasmall uniform carbon dots with excellent performance in bioimaging. Abstract : Fluorescent carbon quantum dots (CQDs) are a new class of carbon nanomaterials that have excellent biocompatibility and low toxicity, useful for cell labeling and bioimaging. However, it is challenging to reproducibly create CQDs that are uniform and small in size with controlled toxicity and fluorescence properties, and this status quo hinders the practical application of CQDs, especially in vivo . In this report, CQDs with a uniform size of ∼1.53 ± 0.42 nm are synthesized via in situ pyrolysis of organics confined in the smallest-pore zeolite SAPO-20 with a micropore aperture of 0.28 nm. The ultrasmall fluorescent CQDs show a bright green fluorescence with a quantum yield (QY) of 16%, higher than that of most of the bare CQDs without any functionalization and maximum emission at 523 nm under the irradiation of xenon-light at an excitation wavelength of 470 nm. X-ray photoelectron spectroscopy (XPS) characterization confirms the presence of rich carboxyl and hydroxyl groups on the CQD surface containing N- and O-based functional groups. The synthesized CQDs with high QY and low cytotoxicity have been successfully used for cellular imaging with excellent biocompatibility.